KONSTRUKSI MAKNA â€œSIMBOL KEABADIANâ€ DALAM FILM BLOOD DIAMOND - Hermawati, Yanti (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2010)
This research is based on the assumption that films do not only show mere entertainment. They have space for various ideological representations. The aim of this research is to reveal how ?the symbol of eternity? has been constructed through ?Blood Diamond?, a Hollywood film. The research uses qualitative method with semiotic approach. The result shows that there are some ?symbols of eternity? contructed in that film, which is Bling Blang versus Bling Bling, This Is Africa (TIA), and Black and White. Bling Blang versus Bling Bling shows that diamond is one of the symbols of eternity which has different meanings for two different countries. In Africa, it is marked by bloodshed. While in America, it is identical with luxury and pride. Meanwhile, TIA is a symbol of eternal significance showing that Africa is often constructed as a rich black continent, but known as areas of conflict, civil war and chaos. Lastly, Black and White in this movie are contructed as two groups that have different social classes.